Using ApoE Nanolipoprotein Particles To Analyze SNARE-Induced Fusion Pores - Bello, Oscar D (Langmuir : the ACS journal of surfaces and colloids, 2016)
Here we introduce ApoE-based nanolipoprotein particle (NLP)-a soluble, discoidal bilayer mimetic of ∼23 nm in diameter, as fusion partners to study the dynamics of fusion pores induced by SNARE proteins. Using in vitro lipid mixing and content release assays, we report that NLPs reconstituted with synaptic v-SNARE VAMP2 (vNLP) fuse with liposomes containing the cognate t-SNARE (Syntaxin1/SNAP25) partner, with the resulting fusion pore opening directly to the external buffer. Efflux of encapsulated fluorescent dextrans of different sizes show that unlike the smaller nanodiscs, these larger NLPs accommodate the expansion of the fusion pore to at least ∼9 nm, and dithionite quenching of fluorescent lipid introduced in vNLP confirms that the NLP fusion pores are short-lived and eventually reseal. The NLPs also have capacity to accommodate larger number of proteins and using vNLPs with defined number of VAMP2 protein, including physiologically relevant copy numbers, we find that 3-4 copies of VAMP2 (minimum 2 per face) are required to keep a nascent fusion pore open, and the SNARE proteins act cooperatively to dilate the nascent fusion pore